Peran Katekis di Era Digital dalam Membina Spiritualitas Umat Allah - Ibius Cerdas Putra Jaya Gulo; Kristiana Mendrofa; Evimawati Harefa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
The development of digital technology brings great opportunities as well as challenges for the development of the faith of Catholics. This article discusses the role of catechists in fostering the spirituality of the people in the digital era using the literature review method. The results show that catechists are required to not only convey the Church's teaching, but also to be present as spiritual companions through digital media such as social media, faith apps, podcasts, and virtual prayer communities. The role of catechists is evolving into creative and contextual content creators, virtual community facilitators, and digital evangelists. However, challenges arise in the form of digital distractions, the spread of misinformation, and reduced face-to-face relationships in the life of faith. With mastery of digital literacy, spirituality, and faith pedagogy, catechists are able to provide relevant and transformative services. This article confirms that catechism in the digital age plays a central role in strengthening the faith of the people and building a deep spiritual community even in a virtual space.